Genome reconstruction of white spot syndrome virus (WSSV) from archival Davidson’s-fixed paraffin embedded shrimp (Penaeus vannamei) tissue - Cruz-Flores, Roberto (Sci Rep, 2020)
Formalin-fixed paraffin-embedded (FFPE) tissues are a priceless resource for diagnostic laboratories worldwide. However, DNA extracted from these tissues is often not optimal for most downstream molecular analysis due to fragmentation and chemical modification. In this study, the complete genome of white spot syndrome virus (WSSV) was reconstructed from ~ 2-year-old archived Davidson’s-fixed paraffin-embedded (DFPE) shrimp tissue using Next Generation Sequencing (NGS). A histological analysis was performed on archived DFPE shrimp tissue and a sample showing a high level of WSSV infection was selected for molecular analysis. The viral infection was further confirmed by molecular methods. DNA isolated from DFPE and fresh frozen (FF) tissues were sequenced by NGS. The complete genome reconstruction of WSSV (~ 305 kbp) was achieved from both DFPE and FF tissue. Single nucleotide polymorphisms, insertion and deletions were compared between the genomes. Thirty-eight mutations were identified in the WSSV genomes from the DFPE and FF that differed from the reference genome. This is the first study that has successfully sequenced the complete genome of a virus of over 300 kbp from archival DFPE tissue. These findings demonstrate that DFPE shrimp tissue represents an invaluable resource for prospective and retrospective studies, evolutionary studies and opens avenues for pathogen discovery.